Assisted child-minding based on visual activity monitoring in a home camera surveillance system - Kam, Joey Teik Kuan (2009)
Taking care of a child can be a very demanding task nowadays. Accidents can occur if the child minder is not paying enough attention. Children might end up being injured or breaking stuff around the house. To help cope with this problem, a system that helps assist the child minder in monitoring the child is being proposed.